Visual analysis of ovarian cancer immunotherapy: a bibliometric analysis from 2010 to 2025 - Zhang, Yingjie; Chen, Yanyan; Chen, Chunru; Cheng, Xiaohua; Peng, Yanan; Wang, Juan; Li, Fuxia; Wenting, Li (Frontiers in Medicine, 2025)
Research on immunotherapy for ovarian cancer is rapidly advancing, and harnessing the immune system to fight tumors is at the forefront of cancer treatment. This article aims to discuss the prospect and development trend of immunotherapy for ovarian cancer from the perspective of bibliometrics. Articles about tumor burden and immunotherapy were collected from the Web of Science Core Collection (WoSCC) (retrieved on 1 May 2025). R package “Bibliometrics” analyzes key bibliometric characteristics and creates a three-filed map to show the relationships between institutions, countries, and keywords. VOSviewer is used for co-author analysis, co-occurrence analysis, and visualization. CiteSpace calculates citation burst citations and keywords. A total of 1,449 publications were retrieved from 15 years of scientific research. The China and United States (US) published the most articles. The most productive journals were Cancer Immunology Immunotherapy and Journal for Immunotherapy of Cancer. The top institution with the highest output was HARVARD UNIVERSITY. In recent years, the hot keywords of strong citation burst strength were “dendritic cells,” “monoclonal antibody,” and “adoptive immunotherapy.” This bibliometric analysis mapped a basic knowledge structure. The tumor burden and immunotherapy field is entering a rapidly growing stage and keeping its value for future research.